Practical Implications of Parabolas - Sah, Shivam Kumar; Sahani, Suresh Kumar; Sahani, Kameshwar (Balai Publikasi Indonesia, 2025)
This project highlights the significance of parabolas in technology, science, and architecture while examining their various everyday uses. Because they can concentrate sound waves at a particular location, parabolic shapes are essential in the construction of satellite dishes, automobile headlights, and flashlights. This project illustrates how mathematics and practical problem-solving structural stability and visual appeal. This project illustrates how mathematics and practical problem solving interact by jamming the uses of parabolas, showing how a straightforward geometric shape can transform technology and enhance everyday life.